EFEKTIVITAS TEKNOLOGI M-BIO PADA PENGELOLAAN LIMBAH PADAT INDUSTRI PENYAMAKAN KULIT SUKAREGANG GARUT 2) 1) UNTUK PERTANIAN RAMAH LINGKUNGAN - Priyadi, Rudi; Iskandar, Rakhmat; Nuryati, Rina; Hermawan, Yoni (Bumi Lestari, 2016)
The objective of the research was to find out the effectiveness of M-Bio technology on the management of solidwaste of tanneryindustry inSukaregang Garutforsustainable agriculture and to obtain the treatmentthat givesthe best results of the  waste management of solid waste of tanneryindustryinSukaregangGarut into organic fertilizer.The research was conductedin theLaboratory ofthe Faculty ofAgriculture, University ofSiliwangiTasikmalayain3 stages. Stage-1was the contact time of M-Bio inthesolid waste with a dose of15ml/L24hours: 48 hours: 72 hours: 96 hoursand120 hours, and thecheck(without treatment ofM-Bio). The parametertested was the Cr content. Stage-2was thecontinuationof thestage-1, toobservethe decreased levels ofCr +6 , i.e.withthe increasingdoses ofM-Bio to 20ml/Lwiththe contacts timeof 10, 15, and20days. The parameters observed werethe content ofCr , N, P, K, andpH. Stage-3 was thefurthertesttoobtainthe besttreatmenttoproduceorganic fertilizer. Thetreatmentwasthe contact times 5, 10, 15 dayswith the doseof M-Bio 8.5;17;25.5;and34ml/ L;so there were12treatmentcombinations. The parameterstested wereCr +6 , total Cr, N,P,K, and pH. The results showedthatthe best treatmentcombinations toreduceCr +6 were thetreatment combinationF(contact time 10days+dose of17ml/LM-Bio) andJ(contact time 15days+dose of17ml/LM-Bio) whichgivesthe lowestCr 6+ 6+ (from 1.21 to 2.56 mg/kg), andgave aquitehigh contentof nitrogen (N) (2.35 to 2.45%), and thecontent ofPhosphorous(P) andPotassium(K) below 0.1mg/kgandbelow0.5mg/kg, andthe pHwas4.55–5.05. It was concludedthat theM-Bio was effectiveandcouldreducetheharmfulCr , so thesolid wasteof tanning industryin Sukaregangcouldbeusedasorganicfertilizerforsustainable agriculture.
Keywords: Cr 1, M-Bio, solid wasteof tanning industry, organic fertilizer, sustainable agriculture.